Bioprospecção de fungos endofíticos da alga vermelha Pyropia spiralis - Costa, Luis Paulo de Sousa [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
This work dealt with the study of fungal strains Sarocladium strictum (Ps-02) e Coniothyrium sp. (Ps-03) associated to the red macroalga Pyropia spiralis, collected at SP State shore. Their extracts were obtained in different culture media: rice, malt and Czapek, which induced diversified metabolic production, as shown by HPLC-DAD and NMR analyses and evidenced that the metabolic profile depends on culture media for these strains. Extracts and fractions from Sarocladium strictum and Coniothyrium sp. were evaluated in antifungal, anticholinesterasic and cytotoxic assays and presented one or more potential bioactivities. Fraction Ps-03 A-ACN from Coniothyrium sp. showed antifungal and cytotoxic activities, and was selected for reversed phase column chromatography under positive pressure and gradient elution with H2O:MeOH. Fractions purification by HPLC-DAD or normal phase column chromatography led to the isolation of one diketopiperazine, polyketides and steroids, which had their structural elucidation by UV, 1D and 2D NMR, and MS analyses. The polyketides isolated in this study include three aromatic macrolides (1 – 3): (3R,5R)-sonnerlactone and two sonnerlactone analogues: one novel compound and one novel as a natural product; the aromatic butenolide gymnoascolide A (4), and the antiviral tetralone 10-norparvulenone (7). Two steroids: ergosterol-5,8-endoperóxido-∆6,22 (5) and 22E-ergosta-7,22-dieno-3β,5,6-triol (6) were also isolated. They are structurally related, probably due to rearrangement, which includes opening of the endoperoxide ring and double bond shift. Compound 8 is a diketopiperazine, that results from one unit phenylalanine and one of threonine. Such results confirm the strong chemodiversity of marine-derived endophytic fungi and their relevant bioactivity potential, which represents an open and attractive path towards deeper bioprospection studies on such ecological niche.

Este trabalho consistiu no estudo dos micro-organismos Sarocladium strictum (Ps-02) e Coniothyrium sp. (Ps-03) associados à macroalga vermelha Pyropia spiralis, coletada no litoral paulista. Os extratos foram obtidos em diferentes meios de cultivos: arroz, malte e Czapek, e induziram produção metabólica diversificada, conforme apontado pelas análises por CLAE-DAD e RMN de 1H, evidenciando que o perfil metabólico é dependente do meio de cultivo para estas linhagens. Os extratos e frações de Sarocladium strictum e Coniothyrium sp. foram avaliados em ensaios para atividade antifúngica, anticolinesterásica e citotóxica e apresentaram uma ou mais potenciais atividades. A fração Ps-03 A-ACN de Coniothyrium sp. apresentou atividade antifúngica e citotóxica, e foi selecionada para fracionamento por cromatografia em coluna sob pressão em modo reverso (C18) com eluição em gradiente H2O:MeOH. A purificação das frações por CLAE-DAD ou cromatografia flash em modo normal levou ao isolamento de uma dicetopiperazina, policetídeos e esteroides, que tiveram suas estruturas determinadas por análises na região do UV, RMN 1D e 2D, e por espectrometria de massas. Os policetídeos isolados neste estudo incluem três macrolídeos aromáticos (1 – 3): a (3R,5R)-sonnerlactona e dois análogos à sonnerlactona, sendo um inédito na literatura e outro, inédito como produto natural; o butenolídeo aromático gymnoascolídeo A (4), e a tetralona antiviral10-norparvulenona (7). Foram também obtidos os esteroides ergosterol-5,8-endoperóxido-∆6,22 (5) e 22E-ergosta-7,22-dieno-3β,5,6-triol (6), estruturalmente relacionados, provavelmente por rearranjo que inclui a abertura do anel endoperóxido e deslocamento da ligação dupla. A substância 8 uma dicetopiperazina: formada por unidades do aminoácido fenilalanina, e outra, do aminoácido treonina. Estes resultados confirmam a expressiva quimiodiversidade de fungos endofíticos de origem marinha, e seu potencial de bioatividade relevante, abrindo perspectivas atrativas para estudos de bioprospecção neste nicho ecológico.
Bioprospection endophytic fungi red alga Pyropia spiralis
Keywords: Fungo endofítico; Alga marinha; Metabólitos; Fungos marinhos; Micro-organismo; Endophytic fungi; Marine alga; Metabolites; Marine fungi; Microorganisms; Los hongos endófitos; Algas; Metabolitos; Los hongos marinos; Microorganismos